florabr: An R package to explore and spatialize species distribution using Flora e Funga do Brasil - Weverton C. F. Trindade (Applications in Plant Sciences)
Abstract Premise The Flora e Funga do Brasil project is the most comprehensive effort to reliably document Brazilian plant and fungal diversity. It involves the collaborative work of hundreds of taxonomists, integrating detailed and standardized morphological descriptions, nomenclatural status, and geographic distribution information of plants, algae, and fungi collected throughout Brazil. Despite the extensive information available, managing the information from the Flora e Funga do Brasil website poses certain challenges. Methods and Results florabr is an R package developed to facilitate the exploration and geographical analysis of species information derived from the Flora e Funga do Brasil. Unique to florabr is its ability to interact with the latest, or any other version of the dataset, which undergoes weekly updates. I illustrate the practical application of florabr in common tasks in biogeography and conservation studies. Conclusions florabr is anticipated to be of significant interest to biogeographers, ecologists, curators of biological collections, and taxonomists actively contributing to the Flora e Funga do Brasil.